2020
DOI: 10.1016/j.envsoft.2020.104717
|View full text |Cite
|
Sign up to set email alerts
|

Predicting seagrass decline due to cumulative stressors

Abstract: Easy-to-use program to predict cumulative light and temperature stress on seagrass Software predictions made from a new process-based model of tropical seagrass decline Model suggests net carbon loss rate controls shoot density decline rate in seagrass Model calibrated to data via two posterior-computation methods for Bayesian inference New generalisable cumulative stress index forecasted by model, including uncertainty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 81 publications
(111 reference statements)
0
50
0
Order By: Relevance
“…To design a marine protection system for all seagrass communities, these spatial complexities and differing sensitivities to environmental conditions would need to be adapted into a broader marine protection approach. We are now able to better evaluate environmental risk to seagrass habitats from natural processes and anthropogenic activity and to assess environmental threats that affect seagrass at a large scale including cyclones and floods 4 , 36 , 58 , climate change 59 , 60 , and more localised impacts such as coastal development, dredging, and oil spills 61 , 62 . Spatial assessments of cumulative anthropogenic risk to seagrasses in the GBRWHA found risks tend to accumulate where ports and coastal development pressures overlay with inputs from coastal catchment runoff 38 .…”
Section: Discussionmentioning
confidence: 99%
“…To design a marine protection system for all seagrass communities, these spatial complexities and differing sensitivities to environmental conditions would need to be adapted into a broader marine protection approach. We are now able to better evaluate environmental risk to seagrass habitats from natural processes and anthropogenic activity and to assess environmental threats that affect seagrass at a large scale including cyclones and floods 4 , 36 , 58 , climate change 59 , 60 , and more localised impacts such as coastal development, dredging, and oil spills 61 , 62 . Spatial assessments of cumulative anthropogenic risk to seagrasses in the GBRWHA found risks tend to accumulate where ports and coastal development pressures overlay with inputs from coastal catchment runoff 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the interaction between stressors is now viewed as a critical issue, and it is suggested that single-factor experiments are not adequate for assessing the effects of several disturbances on coastal marine ecosystems (Wernberg et al, 2012;Todgham and Stillman, 2013;Ontoria et al, 2019b). In the last years, an increasing number of papers aiming to understand cumulative impacts of stressors have exponentially increased (Gunderson et al, 2016;Adams et al, 2020;Stockbridge et al, 2020), and more empirical data on the effects of the interaction of increasing temperature and nutrient over-enrichment at an individual level has been obtained (Touchette and Burkholder, 2002;Bintz et al, 2003;Touchette et al, 2003;Burnell et al, 2013;Kaldy, 2014;Kaldy et al, 2017;Egea et al, 2018;Moreno-Marín et al, 2018;Mvungi and Pillay, 2019;Ontoria et al, 2019b). Nevertheless, responses depend on their local adaptation and life history traits (Tuya et al, 2019;Anton et al, 2020) are species-specific, and to our knowledge, there is very limited information about the combined effects of these two stressors in any tropical seagrasses species (Artika et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(A topographical interpretation of these findings is also provided in the next section.) In this way, we also demonstrated that our methods are well-suited for applications where there is little prior knowledge about the parameter values (14-16, 29) but also for those where prior beliefs can be confidently included as part of the model-data fitting process (6,8,35,36,58,59).…”
Section: Discussionmentioning
confidence: 73%